Contract Archaeology, Social Media and the Unintended Collaboration with the Public — Experiences from Motala, Sweden - Göran Gruber (Internet Archaeology, 2017)
Swedish contract archaeology has a long tradition of making excavation results publicly accessible. Public engagement has often proceeded from the idea that archaeologists are the producers of knowledge and the public are the receivers. Public contacts have chiefly aimed at educating; at the same time, there has been a general interest in legitimising work done on behalf of citizens, largely thanks to public funds. In the last decade, digital technology has become more commonly used as a way to communicate archaeological fieldwork. Through the use of web-based technologies, interactions with the public are getting more diversified in a global, as well as a local, context. This article focuses on the use of social media and how these are intertwined with traditional communication methods in the co-production of narratives concerning historic places. These narratives are used in a range of culturally, socially and/or economically meaningful situations. The article is based on a case study and argues that contract archaeology could better develop its potential to interact with the public; to do so, archaeologists need to gain a much broader understanding of what happens when they communicate, and deeper knowledge of the practice and values underlying social media.